IMMIGRATION POLYTECHNIC BEACH CLEAN ACTION TO SUPPORT ECO-TOURISM DEVELOPMENT AND INCREASE COMMUNITY CARE ABOUT ENVIRONTMENT HYGIENE AROUND WATU KARUNG BEACH AND PANCER DOOR BEACH, PACITAN REGENCY - Muhammad Wildan Arsyad Muzaki; Ale Alfero Deputra; Intan Nurkumalawati (Jurnal Abdimas Imigrasi, 2021)
The rapid development of tourism in Pacitan Regency, in addition to having a positive impact, has also caused various problems, including environmental degradation and environmental pollution due to plastic waste. Watu Karung and Pancer Door beaches are also affected by the beach. One of the main factors that can support the cleanliness of the coast is the existence of pro-active actions from the surrounding community and beach visitors. Therefore, through the 2020 Latjapura activity, the Immigration Polytechnic Cadets carry out community service activities by mutual cooperation around the coast to provide benefits to the community and the surrounding ecosystem and increase awareness of the cleanliness of the surrounding community in order to create a good ecosystem and ecotourism-based beaches. This activity is also expected to provide awareness of the cleanliness of the coastal environment for the surrounding community and provide an understanding to the public that the waste produced has a negative impact on the development of marine biota and ecosystems.